EFFECTIVENESS OF IMPROVING CRITICAL THINKING SKILLS IN PRIMARY CLASS STUDENTS - E. Djumaboyeva; M. J. Makhammatova (Journals Park Publishing, 2023)
In this article, the results of the research aimed at determining the level of development of critical thinking skills of future teachers in the process of training pedagogical personnel in higher educational institutions as a decisive requirement for solving pedagogical problems are widely covered.
Keywords: Critical thinking, intelligence, reasoning, cross-functional skills, adult cognition.